1998
DOI: 10.1007/s002620050513
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological administration of granulocyte/macrophage-colony-stimulating factor is of significant importance for the induction of a strong humoral and cellular response in patients immunized with recombinant carcinoembryonic antigen

Abstract: Eighteen colorectal carcinoma patients without macroscopic disease after surgery were immunized using recombinant (r) human (h) carcinoembryonic antigen (CEA) with (n=9) or without (n=9) the addition of soluble granulocyte/macrophage-colony-stimulating factor (GM-CSF). The dose of rhCEA per immunization was 100 microg (n=6), 316 microg (n=6) or 1000 microg (n=6). rhCEA was given s.c. on day 1 and 80 microg/day of GM-CSF s.c. on days 1-4. The schedule was repeated six times during a period of 9 months. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…16). Our preliminary findings, reported earlier (10), clearly illustrated that a vaccine containing whole CEA protein could reverse any existing anergy and elicit an immune response. The intrinsic immune reactivity toward a self-antigen such as CEA, however, is very minimal.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…16). Our preliminary findings, reported earlier (10), clearly illustrated that a vaccine containing whole CEA protein could reverse any existing anergy and elicit an immune response. The intrinsic immune reactivity toward a self-antigen such as CEA, however, is very minimal.…”
Section: Introductionmentioning
confidence: 78%
“…We therefore adapted the present study to include repeated immunizations and a potent adjuvant-like GM-CSF to break the anergy/ unresponsiveness toward CEA (17). We have previously reported that GM-CSF given as an adjuvant substantially augmented both cellular and humoral immune responses against the rCEA protein (10,18). The capacity of GM-CSF to augment an antitumor immune response is most likely due to the ability to enhance antigen presentation by dendritic cells in vivo (19 -21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Patients with colon cancer immunized with rCEA mounted both antibody and T-cell responses against CEA that were enhanced by adding granulocyte/macrophage-colony-stimulating factor (GM-CSF). 15 Unlike several infectious diseases, which are well controlled by humoral responses, solid tumors such as colon carcinoma are likely to require cellular responses for effect. Studies in animals reveal that tumor regression is more often associated with cellular than with humoral immunity.…”
mentioning
confidence: 99%
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF) is known to expand myeloid-derived dendritic cell (DC) populations (20,47), to augment antigeninduced humoral and cellular immune responses, and to affect the Th1/Th2 cytokine balance (45). It has been extensively used as an effective genetic and protein adjuvant to enhance immunogenicity of tumor and vaccine antigens (6,14,16,28,29,31,35,42,48,50,54,56). Another immunostimulatory molecule is CD40 ligand (CD40L), which is a surface molecule primarily expressed on mature CD4 ϩ T cells.…”
mentioning
confidence: 99%